Increasing trammel mesh size reduces biomass removal, mitigates discards and increases economic revenue in artisanal fisheries - Tarantino, Giulio; Motta, Gregorio; D’Ambrosio, Paolo; Felline, Serena; Sbragaglia, Valerio; Bevilacqua, Stanislao; Tedesco, Perla; Scordella, Giuseppe; Terlizzi, Antonio (Frontiers in Marine Science, 2024)
Small-scale fishing plays a major role in regional economies worldwide and, with a large number of small vessels involved, it provides employment and livelihood to coastal communities. Generally recognized as more selective than other fishing practices, small-scale fishery can nevertheless be subjected to high rates of discards of both non-target species and small-sized individuals, which in turn could lead to both decreased incomes for fishers and increased depletion of fish stocks. However, if the relationship between fish size and price has long been assessed, the effect of enhanced size-selectivity of fishing gears and consequent economic gains has been little investigated. This study, set in the Porto Cesareo Marine Protected Area (Italy, Ionian Sea), aimed at testing effective strategies to improve trammel net selectivity, reducing discards and maximizing the income for fishers. Different mesh sizes (20, 22 and 24 mm) trammel nets were employed. The study consisted in 72 fishing days from July 2012 to September 2013 and each day involved experimental fishing with the three mesh sizes. A total of 16008 specimens (103 species) were collected but the analysis focused on the 18 most common species in the area for a total of 12782 individuals. Mesh size trammel nets of 20 mm and 22 mm yielded most of the biomass, 324.8 and 321.5 kg respectively, while the 24 mm mesh yielded 280.7 kg. The 24 mm mesh, even if accounted for lower income compared to the 22 mm mesh (2383.9 € vs 2590.5 €, respectively), provided significant 50% reduction of discards compared to the 20 and 22 mm mesh. The use of 24 mm mesh size was found to be an effective strategy to reduce the number of discarded organisms and, consequently, the pressure exerted on local fish stocks with associated higher revenue for fishers. The results of this study demonstrated that trammel net selectivity can improve and support conservation measures and concurrently increase profitability of local fishery.